Оптимізація режимів роботи електромеханічних систем зерноочисних агрегатів - Карпова, О. П.; Постнікова, Марина Вікторівна; Постникова, Марина Викторовна; Postnikova, Marina (My University, 2017)
UK: Виконано дослідження оптимізаційних режимів роботи електромеханічних систем зерноочисного агрегату ЗАВ-40 з використанням теорії планування математичного експерименту з пошуком оптимальних значень функції цілі. В основу досліджень покладено положення теорії планування математичного експерименту. Отримано адекватні рівняння регресії другого порядку параметра оптимізації в функції змінних факторів, що дозволило визначити мінімальні питомі витрати електроенергії при очищенні зерна агрегатом ЗАВ-40. Вперше отримано залежності питомих витрат електроенергії агрегатом ЗАВ-40, які забезпечують оптимізацію питомих витрат електроенергії при дотриманні агротехнічних вимог до якості очищеного зерна. Запропонована методика дозволила одержати мінімально можливі значення питомих витрат електроенергії на потокових лініях агрегату ЗАВ-40 з урахуванням впливу змінних факторів. Це дозволило розробити науково-обгрунтовані норми витрати електроенергії для технологічних схем очищення зерна агрегату ЗАВ-40. RU: Выполнено исследование оптимизационных режимов работы электромеханических систем зерноочистительного агрегата ЗАВ-40 с использованием теории планирования математического эксперимента с поиском оптимальных значений функции цели. В основу исследований положены положения теории планирования математического эксперимента. Получены адекватные уравнения регрессии второго порядка параметра оптимизации в функции переменных факторов, что позволило определить минимальные удельные расходы электроэнергии при очистке зерна агрегатом ЗАВ-40. Впервые получены зависимости удельных расходов электроэнергии агрегатом ЗАВ-40, которые обеспечивают оптимизацию удельных расходов электроэнергии при соблюдении агротехнических требований к качеству очищенного зерна. Предложенная методика позволила получить минимально возможные значения удельных расходов электроэнергии на поточных линиях агрегата ЗАВ-40 с учетом влияния переменных факторов. Это позволило разработать научно-обоснованные нормы расхода электроэнергии для технологических схем очистки зерна агрегата ЗАВ-40. EN: To study the optimization modes of the electric drives of the study of the theory of planning a mathematical experiment under multi factorial influence with oh the search for optimal values of the objective function on the basis of adequate mathematical models in the form of regression equations of the second order; to find operation modes of the follow lines grain cleaning, which in the range of changes in input parameters have provided a minimum of specific energy consumption. The basis of the problem of further improvement of past-harvesting of grain in the conditions of farms is the task of improving the quality of the final product and reducing the energy intensity of the process. Methodology. To conduct the research, the theory of the mathematical experiment planning has been used. Results. The corresponding regression equations of the second order optimization parameters have been received for electricity consumption for technological process of grain cleaning in the function of variable factors; performance grain cleaning unit, power consumption and coefficient download electric motors streaming line treatment drain that allowed determining the minimum specific electricity consumption in ZAV-40 cleaning grain unit. Originality. For the first time dependencies of specific electricity consumption have been calculated taking into account the actual loading of electric motors which ensure optimization of specific electricity while complying with agro technical requirements for the quality of purified grains. Practical value. The proposed method has allowed to get the lowest possible values unit costs electricity at ZAV-40 cleaning grain streaming lines grain-harvesting unit taking into account the influence of variables. It has allowed develop scientifically grounded norms of specific electricity consumption for technological schemes of grain purification on ZAV-40 unit, which have been discussed and approved by the technical council of the Zaporizhzhia District, Melitopol Regional Department of Agriculture and Velikolepetiskii District Agricultural Department of Kherson region.
Оптимизация режимов работы электромеханических систем зерноочистительных агрегатов
Optimization of the operating mode of the electric mechanical systems of the grain cleaning machines
Keywords: енергозбереження; електропривод; економія електроенергії; нормування електроенергії; багатофакторний експеримент; планування експерименту; энергосбережение; электропривод; экономия электроэнергии; нормирование электроэнергии; многофакторный эксперимент; планирование эксперимента; energy saving; electric; regulation of electricity; multivariate; experiment; planning experiment